Potential Surface Analysis (PSA) for Urban Development in Samutsakorn, Nakornpathom, Samutsongkram, Petchaburi and Huahin, Prajuabkirikhan - Ativitavas, Pornpat; Thongsukplang, Suwadee (Journal of Architectural/Planning Research and Studies (JARS), 2006)
This article presents the study of Potential Surface Analysis (PSA) which is a technique to rank spatial factors upon which influence an urban development and to calculate factor scores to find a suitable area for an urban development. This technique is prevalently used in various fields of studies in the past decade such as geography, environmental science, landscape architecture and urban planning. In this analysis, the collective geographic information system database was derived from several organizations of Thailand and was analysed by an ArcView program. The issue in this article is a part of a primary analysis which focuses only on physical factors; meanwhile excluding factors in socio-economic and infrastructure in engineering, which are otherwise important in an urban development, which should be incorporated in a next step of the study.